Prinsip-prinsip dalam Pengembangan Kurikulum - Arif Rahman Prasetyo; Tasman Hamami (PALAPA, 2020)
Curriculum development is an important thing to do. In Indonesia, there have been ten curriculum changes that have started from the 1947 Curriculum to the present, the 2013 Curriculum. In fact, the curriculum changes show that the principles of education must be able to adjust the development of the times without leaving the cultural values of the relevant community. The purpose of this research is to find out the principles in curriculum development. This research uses library research method. The results of this study indicate that curriculum development resources, including; empirical data, experimental data, folklore and general public knowledge. The principles in curriculum development are divided into two things: 1. General Principles, which include; the principle of relevance, the principle of flexibility, the principle of continuity, the practical principle, and the principle of effectiveness, 2. Special Principles, which include; principles for determining educational objectives, principles for selecting educational content, principles for selecting teaching and learning processes, principles for selecting media and teaching tools, and principles relating to assessment.